The Use of Psychological Diagnostics in the Military System and its Specific Aspects - Ne'matovich, Arzikulov Dilshod (European Journal of Life Safety and Stability (2660-9630), 2023)
This article discusses the use of psychological diagnostics in the military system and its specific aspects, the emergence of psychodiagnostic tools developed on the basis of scientific principles to determine the aspects of people's suitability for work in the world psychological practice, and stated the researches carried out by foreign scientists on the use of psychodiagnostics in the military field.